The Ethical Commitment of Medicine: in relation to the work of Alfred I. Tauber - Arrieta-Valero, Ion (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
Taking as starting point the recent translation into Spanish of his book Confessions of a medicine man, his most personal and applauded work, this article reviews the work of Alfred I. Tauber, one of the most influential voices currently in U.S. medical humanities. Tauber’s work is already very extensive and presents a wide variety of themes, but it is possible to identify two main concerns: the attempt to justify and implement an alternative to autonomist ethics that today dominates the medical practice and decision making on the one hand; and on the other hand, the concern for the excessive penchant for science and technology that usually shows current medicine, which would have nothing objectionable if it had not sacrificed in a clumsy and unnecessary way the empathetic and humanist element characteristic of the art of caring.